Difficulties Experienced by Prospective Teachers of Psychology during the Teaching Practice - Lazdauskas, Tomas; Saikauskienė, Albina (Pedagogika, 2015)
The analysis of reflections submitted in the reports about the teaching practice of the prospective teachers of psychology is presented in the article. The main purpose of this analysis is to reveal the difficulties experienced by prospective teachers of psychology during their teaching practice. The reports about the teaching practice, issued by the fourth-year students (N = 44), studying according to the syllabus of psychology at the full-time department, were selected for analysis. The thematic analysis method was applied for analysis of reflections; the difficulties experienced by the students during their teaching practice, serve as the unit of analysis. The results of the investigation proved that all students experience difficulties while planning and / or delivering the lessons during their practice. 149 statements, reflecting the difficulties, experienced during the teaching practice, are field in reflections of the students. The thematic analysis of the students’ reflections allowed singling out seven main themes, which define the experienced difficulties to the best extent, i.e. the material (14.77 %), methods (20.81 %), class management (27.52 %), knowledge / competences (4.03 %), emotions (10.07 %), time management (18.12 %) and organization of work (4.70 %). The themes and sub-themes, which were singled out, allow foreseeing the spheres of the content of the pedagogical studies, to which the utmost attention must be devoted, seeking for improvement of the quality of studies. These themes are discussed in the context of the other investigations in the present article; the possibilities of perfection of preparation of the teachers of psychology are discussed and the guidelines for further investigations are foreseen herein.